Prediction of Cross-Link Density of Prevulcanized Latex Using InGaAs NIR Spectroscopy - Suntaree Dachapan; Khwantri Saengprachatanarug; Arthit Phuphaphud; Panmanas Sirisomboon; Chin Hock Lim; Jetsada Posom (ACS Omega, 2026)
values of 0.96 and 0.95, respectively. Comparable performance between contact and noncontact instruments further confirmed the practicality of noncontact NIR measurement. This work demonstrates, for the first time, that combining InGaAs NIR spectroscopy with process variables enables accurate, rapid, and nondestructive forecasting of TSI-based cross-link density for PV latex manufacturing.
Keywords: Spectroscopy and Chemometric Analyses; Photovoltaic System Optimization Techniques; Fault Detection and Control Systems